Study of synergistic effect of combined application of tebuconazole with two biocontrol agents for management of Fusarium crown rot in durum wheat - Oulmi, Abdelmalek; Bencheikh, Amor; Mamache, Walid; Gharzouli, Asma; Barkahoum Daichi, Meriem; Rouag, Noureddine (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The in vitro and growth chamber, tests were conducted in order to assess the effects of B. amyloliquefaciens B18 and B. subtilis S8 strains each alone and in combination with tebuconazole against F. culmorum (FC) isolate responsible of Fusarium crown rot (FCR) in durum wheat. The in vitro growth of B18 and S8 strains was unaffected by 30 µg.mL-1 tebuconazole. The Bacillus strains (at 106 CFU.mL-1) and tebuconazole, each alone, reduced the mycelial growth, this effect was significantly improved when they were combined (inhibition of more than 92 %). In growth chamber experiments, efficacy against FCR was significantly higher when integrating Bacillus strains and tebuconazole than by either alone; control efficacy of tebuconazole at 30 µg.mL-1 in combination with S8 and B18 strains reached 90.91 and 95.45 %, respectively. The obtained results indicated that combination of tebuconazole with the biocontrol agents B18 and S8 synergistically improved control efficiency of the fungicide against FCR of wheat.